A second 'Maracanazo'? The 2014 FIFA World Cup in historical perspective. Issue 5 (4th May 2017) - Moore, Kevin
Abstract: This paper seeks to evaluate the 2014 FIFA World Cup in relation to the World Cup tournaments since the first in 1930, in terms of the success of the tournament, both on and off the pitch. The 2014 FIFA World Cup was characterized in the international media for several years prior to the tournament as one which was highly problematic in terms of its organization in Brazil, as to whether the stadia and other infrastructure would be ready. This negativity was compounded after the street protests around the 2013 FIFA Confederations Cup, leading to fears that the 2014 tournament would be marred by significant popular political opposition. Once the 2014 World Cup began and it was clear that the infrastructure was sufficiently in place and the protests would in fact be very minimal, the international media did a swift volte-face and instead portrayed the tournament as a great success. As an historian I take the long view, evaluating the 2014 tournament in the full historical perspective. In doing so, I debunk the media myths about the 2014 FIFA World Cup.